Organogenesis Kelapa Sawit (Elaeis guineensis Jacq.) Asal Eksplan Bunga Betina - Tyas Larasati; Suci Rahayu; Fauziyah Harahap (JBIO: jurnal biosains (the journal of biosciences), 2016)
The objectives of this research were to composed organ from callus culture and to found the best concentration of plant growth regulator for organ growth from female flower explant of oil palm. This research has already done from June 2014 to May 2015 at Laboratory of Plant Physiology and Tissue Culture Department of Biology Faculty of Mathematics and Science University of North Sumatera. This research used Nonfactorial Completely Random Design. Explant was treated with five concentrations of 2,4-Dichlorophenoxy acetic acid (2,4-D; 99, 110, 120, 132, and 140 mg/L) for callus induction on Y3 medium (Eeuwens 1976). The result of this research showed that organ was formed from this treatment (basal segment of female flower explant) was root organ. 2,4-D plant growth regulator positively affected to growing of the root. The best result for time of callus induction, time of root growth, the highest percentage of explants that formed the root, fresh weight and dry weight of callus that has become the root generation was resulted from 99 mg/L 2,4-D.   Key words: Elaeis guineensis Jacq., female flower, plant growth regulator 2,4-D, organogenesis